Security and Fault Tolerance in Internet of Things - Chakraborty, Rajat Subhra; Mathew, Jimson; Vasilakos, Athanasios V. (Internet of Things, Technology, Communications and Computing,, 2019)
This book covers various aspects of security, privacy and reliability in Internet of Things (IoT) and Cyber-Physical System design, analysis and testing. In particular, various established theories and practices both from academia and industry are presented and suitably organized targeting students, engineers and researchers. Fifteen leading academicians and practitioners wrote this book, pointing to the open problems and biggest challenges on which research in the near future will be focused.